Association of age to nutritional status and muscle mass in children with transfusion-dependent β-thalassemia: a cross-sectional study - Wang, Li; Zhang, Luyang; Yang, Yanlan; Luo, Yuan; Wang, Lei; Patil, Sandip (Frontiers in Nutrition, 2024)
Background: Transfusion-dependent β-thalassemia (TDT) is a hereditary blood disorder that often leads to complications affecting growth, nutritional status, and muscle mass in children. This study aims to investigate the associations between age, nutritional status, and muscle mass in children with TDT, providing insights into the progressive impact of age on these parameters. Methods: 122 children with TDT from March 2023 to March 2024 were enrolled in this cross-sectional study. Their nutritional status was assessed using the 2006-2007 World Health Organization (WHO) Growth Charts, and their muscle mass was measured using bioelectrical impedance analysis (BIA). Data related to age, gender, weight, height, fat-free mass (FFM), skeletal muscle mass (SMM), and soft lean mass (SLM) of children were collected for comparative analysis from the hospital record room. Furthermore, Spearman's rank correlation coefficients and regression analyses were utilized to investigate the associations between age and both nutritional status and muscle mass. Results: The results of this study revealed negative correlations between age and wasting (r=-0.26, p<0.001), stunting (r=-0.28, p<0.001), FFM (r=-0.3, p<0.001), SMM (r=-0.23, p<0.01), and SLM (r=-0.36, p<0.001). The regression analysis indicated that age was an independent predictor of wasting, stunting, and reduced muscle mass in these children (all p<0.001).Our study observed a trend of worsening stunting, wasting, and muscle loss in children with TDT as they age. These findings highlight the importance of monitoring both nutritional and muscular health in TDT patients. Early detection and comprehensive nutritional management may improve outcomes in this population.